Assessment of Opioid Overdose Risk and Response Readiness Among Patients at a Clinic for Uninsured Patients - Benjamin Wrucke; Stephen Stevanovic; Naisarg Vanani; Ryan Klauck; Bryan Johnston (Journal of Student-Run Clinics, 2024)
Background: The opioid epidemic has been worsening. Fortunately, studies show that bystanders can effectively administer naloxone to reverse opioid overdose, and overdose education programs result in improved ability to respond to overdose. However, there has been limited research investigating opioid overdose risk and response preparedness among patients without insurance. This descriptive report aimed to assess risk of opioid overdose among patients without insurance in addition to their family members and close contacts and assess whether these patients, as crucial bystanders, were prepared to respond to opioid overdose.Methods: Patients without insurance at a student-run free clinic completed an anonymous, voluntary survey during in-person appointments. Data were collected for eight months from 2021-2022. One-proportion Z-test compared respondent rates of opioid use with overall statewide community rates reported by the Wisconsin Department of Health Services (DHS) Opioid Dashboard. Subgroup analysis further described the data collected, and hypothetical number needed to screen (NNS) calculations explored possible screening methods for naloxone distribution.Results: Seventy-two patients responded to the survey. The past-year rate of medically prescribed opioid use in the study population (12.5%) did not differ from the rate statewide (15.8%; p=0.44). Zero respondents reported personal opioid overdose in the past year, but six overdoses had been witnessed. Among respondents with family or close contacts who use opioids, 50% of those respondents who do not carry naloxone do not know where to get it, but 75% of those respondents who are not trained on how to respond to overdose would like to be. Lastly, screening for family or close contact opioid use offered the lowest hypothetical NNS of screening methods considered.Conclusions: Patients without insurance at student-run free clinics, including those with family members or close contacts who use opioids, likely represent a target population for opioid overdose education and naloxone distribution.